Percutaneous Transhepatic Cholangiography with Chiba’s Needle - Nuchowich, Gustavo; Beguiristain, Alberto; Navarro, Teodoro; Abascal, Winston; Praderi, Raúl (Cirugía del Uruguay, 1980)
Fifty jaundiced patients were studied by percutaneous transhepatic cholangiography with Okuda's method, the biliary tree was visualized in 94 o. There were 100 % of good results with dilated biliary ducts (36 cases) and 78 % with non dilated ones ( 11 cases). There was no significative complications.